Targeting the neuroimmune axis in glioblastoma: emerging strategies for precision immunotherapy - Lang, Xiaoling; Zhang, Suming; Wang, Yuhe (Frontiers in Immunology, 2025)
Glioblastoma (GBM) is the most common and fatal primary brain malignancy in adults, and therapeutic gains have been modest despite multimodal standard care. Immunotherapy offers a promising alternative, yet its performance in GBM is constrained by a profoundly immunosuppressive neuro-immune micro-environment, the physical and functional barriers of the blood–brain interface, and adaptative resistance pathways. In this review we summarise recent progress in myeloid-reprogramming agents, immune-checkpoint modulation, adoptive cellular therapies and device-enabled delivery platforms that seek to revitalise anti-tumour surveillance within the central nervous system. We also discuss enduring challenges—including intratumoural spatial heterogeneity, limited effector lymphocyte trafficking and the scarcity of robust predictive biomarkers—that temper durable responses. By thoughtfully integrating immunologic approaches with radiotherapy, anti-angiogenic agents, metabolic modifiers and focussed-ultrasound-mediated blood–brain-barrier disruption, emerging strategies aspire to enhance immune infiltration, bolster antigen presentation and overcome region-specific barriers. Our synthesis provides an appraisal of the evolving landscape of precision immunotherapy for GBM, offering perspective on future directions and avenues for clinical translation. We hope these insights will assist researchers and clinicians as they endeavour to develop more effective and individualised treatment regimens for patients confronted with this formidable disease.